The perception of corporate social responsibility and its influence on the positioning of the SODIMAC brand in Tacna, 2019 - Moreyra Flores, Alvaro Rodrigo (2022)
The research was carried out in order to establish to what extent the perception of Corporate Social Responsibility (CSR) and its influence on the positioning of the SODIMAC brand in Tacna - 2019. There was a sample of 384 people, the technique to collect data was the survey and the instrument was the questionnaire; The sample consisted of clients of the SODIMAC company, located in Tacna and applied to people over 18 years of age. An important finding is that CSR has a significant relationship in the differentiation, identification and recall of the SODIMAC brand, since, in the Spearman correlation coefficient, a strong relationship was obtained in each of the dimensions with respect to CSR. It is established that CSR is significantly related to the Positioning of the Brand, inferring that the principles for the preservation and increase of the well-being of customers and society are closely associated with the way in which a good or service in the minds of SODIMAC customers, emphasizing that it is about the perception of attributes that occupy a place in their minds, represented by a Spearman Rho of 79.4%.